Implementation of Character Education Based on Islamic Boarding Schools in Musical Arts Education in Hasyim Asy'ari University, Jombang - Rochmania, Desty Dwi; Pratiwi, Emy Yunita Rahma; Wiyadi, Heru (Jurnal Pendidikan dan Pengajaran, 2022)
Hasyim Asy'ari University is a pioneer university in Indonesia based on Islamic boarding schools which was built with intelligence of the heart, and maximizes all the potential of human intelligence (multiple intelligences), so that it is able to give birth to a superior generation who has faith, has noble character, and masters science and technology correctly and correctly. useful in society and the nation, but it is very ironic when this goal has not been achieved, because what happens in the field, there are still many students who do not understand the importance of lectures and there is still low awareness of the learning environment such as lack of discipline, being late for class, chatting during lectures, responsibility for college assignments is low, especially in music education courses. The author's goal is to implement Islamic boarding school-based character education in music education, which is expected to be able to revolutionize the mentality of students. The writing procedure used is the Kemmis & Taggart model class action writing, collaborative writing. This writing uses descriptive analysis method. The results of the implementation of Islamic boarding school- based character education in learning music education in the beginning received a poor response from students, but after walking students experienced changes in attitudes and behavior, and began to know the importance of studying and studying. The conclusion of this paper is that through the implementation of Islamic boarding school-based character education in music education courses, it is able to instill character values in students, these character values include; independence/toughness, cooperation, honesty and discipline as well as being active and diligent in studying.Â